Purification and properties of Escherichia coli dimethyl sulfoxide reductase, an iron-sulfur molybdoenzyme with broad substrate specificity. - Weiner, J H (1988)
Dimethyl sulfoxide reductase, a terminal electron transfer enzyme, was purified from anaerobically grown Escherichia coli harboring a plasmid which codes for dimethyl sulfoxide reductase. The enzyme was purified to greater than 90% homogeneity from cell envelopes by a three-step purification procedure involving extraction with the detergent Triton X-100, chromatofocusing, and DEAE ion-exchange chromatography. The purified enzyme was composed of three subunits with molecular weights of 82,600, 23,600, and 22,700 as identified by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The native molecular weight was determined by gel electrophoresis to be 155,000. The purified enzyme contained 7.5 atoms of iron and 0.34 atom of molybdenum per mol of enzyme. The presence of molybdopterin cofactor in dimethyl sulfoxide reductase was identified by reconstitution of cofactor-deficient NADPH nitrate reductase activity from Neurospora crassa nit-I mutant and by UV absorption and fluorescence emission spectra. The enzyme displayed a very broad substrate specificity, reducing various N-oxide and sulfoxide compounds as well as chlorate and hydroxylamine.